Study on the mechanism of Y doping effect for improving the properties of ZnO thermoelectric ceramics. (15th July 2022) - Feng, Bo; Li, Guangqiang; Kong, Dong; Xu, Chenhui; Kuang, Zhixiang; Ma, Yan; Chen, Zhuo; Li, Yawei; Gu, Huazhi; Fan, Xi'an
Abstract: The oxygenated ZnO samples have been prepared by powder metallurgy, and ZnO is doped with high-valence Y element as electron donors. The study found that the electrical conductivity increased significantly, which is mainly due to the increase of carrier concentration upon Y doping. Y doping would widen the band gap, introduce impurity levels, and enhance the density of states near the Fermi level. The Seebeck coefficient decreases due to the increase of carrier concentration, and the power factor shows an upward trend. Due to the enhancement of phonon scattering after Y doping, the lattice thermal conductivity decreases. Finally, ZT was promoted from 0.009 of the pristine sample to 0.427 of the Y doped at 873 K. Graphical abstract: With the substitution of Y, the density of states near the Fermi level is significantly enhanced, and ZT is promoted from 0.009 of the pristine sample to 0.427 at 873 K. Image, graphical abstract